A Conversation Analysis of Adjacency Pairs in the Ellen DeGeneres’s Talk Show with Malala Yousafzai - Trihartina Tampubolon (Journal of Language Learning and Research (JOLLAR), 2019)
This research aims to find out the application of the types of adjacency pairs in a conversation script “Malala Yousafzai” in talk show of Ellen DeGeneres. The writers used the conversation analysis approach to support research in analyzing data. Conversation analysis (CA) is the natural conversation that has participants two or more. Adjacency pairs is paired utterances by two different speakers. The method used is qualitative descriptive. The writer took the data from the “Malala Yousafzai” conversation script on Ellen DeGeneres’s talk show. The data containing video and script, the duration is 8:09 minutes. This video is downloaded from http://www.eamus.it/videos/malala-at-ellens.htm. The writer analyzed the data by reading the script of the conversation and then classified the data according to the types of adjacency pairs. And then drawn conclusion. Adjacency pairs creates an obvious meaning in social interaction through conversation. Adjacency pairs has types and patterns. The pattern determines the meaning being delivered and minimize the misunderstanding between participants. And help people understand what people want to make particular language choices and what people mean. There are six types of the adjacency pairs found in “Malala Yousafzai” conversation script in Ellen DeGeneres’s talk show.